2015
DOI: 10.1159/000371555
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Multidrug Resistance Transporter ABCB5 in a Murine Model of Human Conjunctival Melanoma

Abstract: Conjunctival melanoma (CM) is a rare ocular malignancy with a high tendency to reoccur locally and with a high risk of metastatic disease. Metastases are often unresponsive to conventional treatment. Recently, an animal model was set up using human CM cells. Orthotopic xenografts from human CM were created by subconjunctival injection of three different CM cell lines into NOD.Cg-Prkdcscid IL2rgtm1Wjl/SzJ (NSG) mice. Subconjunctival injection of cultured CM cells led to excellent subconjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
(45 reference statements)
2
8
0
1
Order By: Relevance
“…In addition, in previously published studies, subconjunctival injection of 0.4 × 10 6 conjunctival melanoma cells (i.e. a dose similar to that of the ABCB5 + LSCs in the present study) to NSG mice resulted in ocular tumor development in 100% of the animals [75,76]. Together, these ndings con rm the ocular tumor susceptibility of the animal model used, which, in turn, counts against a tumor risk of treatment with ABCB5 + LSCs.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, in previously published studies, subconjunctival injection of 0.4 × 10 6 conjunctival melanoma cells (i.e. a dose similar to that of the ABCB5 + LSCs in the present study) to NSG mice resulted in ocular tumor development in 100% of the animals [75,76]. Together, these ndings con rm the ocular tumor susceptibility of the animal model used, which, in turn, counts against a tumor risk of treatment with ABCB5 + LSCs.…”
Section: Discussionsupporting
confidence: 85%
“…The results in vitro were expected as CRMM-1 and CM2005.1 harbor a B-RAF V600E mutation, while the CRMM-2 cell line contains an N-RAS Q61L mutation. 17,27 Vemurafenib was approved in 2011 by the Food and Drug Administration for treatment of unresectable melanoma harboring B-RAF V600E mutations 43 and is a potent agent for and P values were as follows: *P < 0.05, **P < 0.01, ***P < 0.001. For all groups: n ‡ 51. treatment of B-RAF V600E-positive melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has shown that two of three available CM cell lines, CRMM1 25 and CM2005.1, 26 harbor a B-RAF V600E mutation, while the third, CRMM2, contains an N-RAS Q61L mutation. 17,27 We injected stable red fluorescently labeled (lentiviral tdTomato-blas) CM cells via different routes into the embryonic zebrafish. Thus, we determined the most effective engraftment strategy for the establishment of CM xenograft tumors in zebrafish and we observed distinct phenotypes after implantation of the three CM cell lines.…”
mentioning
confidence: 99%
“…These cells were grown in RPMI 1640 Dutch modified media (Gibco) supplemented with 10% FBS (Greiner Bio-one), 1% GlutaMAX and 1% Penicillin/Streptomycin (Gibco). Our previous studies [ 49 , 50 ] have shown that CRMM1 and CM2005.1 harbor a BRAF V600E mutation, and CRMM2 contains an NRAS Q61L mutation. These mutations were confirmed at Erasmus University Medical Center, Rotterdam in May 2016 by next generation sequencing (NGS).…”
Section: Methodsmentioning
confidence: 99%